NEUROMARKETING IN THE DIGITAL AGE: HARNESSING NEUROSCIENCE FOR EFFECTIVE ONLINE ADVERTISING - Loso Judijanto; Mohammad Ahmad Bani Amer; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the ever-evolving digital era, neuromarketing is emerging as an innovative approach that combines neuroscience with marketing strategies to improve the effectiveness of online advertising. The review in this research uses the literature method. The results show that neuromarketing has significant potential to improve the effectiveness of online advertising, but its application must be balanced with strong ethical considerations. In conclusion, neuromarketing in the digital age offers a great opportunity for marketers to create a more personalised and effective advertising experience, provided it is implemented with a responsible approach and focuses on adding value to consumers.